PROSPECTS AND CHALLENGES OF RESCUING THE SHRINKING LAKE CHAD THROUGH THE UNITED NATIONS’ GREEN CLIMATE FUND - DAIYABU HASSAN MUHAMMAD (International Studies Journal)
Since the 1960s the Lake Chad has shrunk by about 90% of its original size primarily because of climate change. Some studies have estimated that if the current trend continued, the Lake could disappear in the next few decades. From the 1980s, attempts have been made by the Lake Chad Basin Commission (LCBC) to rescue the shrinking Lake. The most viable plan is the idea of an inter-basin water transfer (IBWT), developed by the Italian Engineering Company Bonfica which involves diverting about 4% of the waters of the tributaries of River Bongi in the Democratic Republic of Congo (DRC) that discharge into the Atlantic Ocean through a series of canals and dams to River Chari (that feeds the Lake) in the Central African Republic (CAR). The current estimate for the project stands at fourteen billion U.S dollars ($14b). Raising the fund by the LCBC to execute the project has become the major obstacle to the realization of the project. Although there is a new initiative by the Italian government and the Chinese construction company PowerChina in partnership with Bonfica to resurrect the idea, the paper argues that the LCBC has failed to access and utilize the adaptation facilities under the United Nations adaptation funds. Drawing from the argument of the justice for international adaptation framework, the paper assesses the vulnerabilities and opportunities of the Lake Chad countries and conclude that, to bring the IBWT to fruition, the LCBC and the riparian states of the Lake Chad must explore and access all available sources of fund, especially the Green Climate Fund.